Kinerja Badan Lingkungan Hidup Dalam Pengelolaan Limbah Batik di Kota Pekalongan - Wahyu Hidayat; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Batik manufacture in Pekalolang City, in real fact create a bad impact for ervironment because of batik sewage, therefore the environment is contaminating around. Performance from Evnironmental Agency in Pekalongan City that handle sewage batik pollution problem ,want to value how the performance that have done and aspects from proponent and obstacle factors in managing sewerage system of batik in Pekalongan City. From explanation above, this study wants to analyze the performance from Environmental Agency of Pekalongan and to determine the proponent and obstacle factors.This study uses consept oprasionalization from five performance dimension, that are productivity, service quality, responsivity, responsibillity, and accountability. The collecting data tehnic is from observation, interview, and bibliography study with Environmental Agency of Pekalongan City employee. The performance from Environmental Agency of Pekalongan City in managing sewerage system of batik sewage, have been composed well and have found the obstacle factors like limited fund, Pekalongan City, and lack of awarness from human resources. Whereas the supporting factors are discipline, waste water treatment plant (WWTP) production, and usage of Clean Production System.